Improving Work System by Reducing Setup Time Activity in Drying Room in Pharmaceutical Industry with Single Minutes Exchange Die (SMED) - M Yani Syafei; Tisa Lokadipati LS (President University, 2018)
Pharmaceutical industry especially that move in generic products, have many kinds of products to be manufactured in its production lines with the shortest possible time. This condition causes the frequent of changeover process. This cause requires the company to further improve the effectiveness of the machine by reducing the time of changeover process in terms of setup and clean-up machine. In order to reducing the time of setup and clean-up activity use the method of approaches the SMED analysis method to reduce unnecessary motion waste (value added and non-value added derived from lean manufacturing). Before conduct the research, in the 5th production line was not in the Kanban system. So, it often occurs the changeover process. The longest changeover time is in the drying room. After that conduct the Time and Motion Study in order to know the detail setup activities in the drying room. This is due to problems in the working methods and environment factors. Based on data from observations made on the engine FBD, there are 49 activities comprising 44 internal activities and 5 activities that can be converted to an external. Then from 44 internal activities, only 43 were able to be combined activity of up to 11 activities. Results from this study is able to decrease setup time and clean-up on the machine FBD by 62.18%. Based on this result also, this can increase the productivity of the production line.Keywords: Unnecessary motion waste, Lean Manufacturing, Value added, Non-value added, Changeover process, SMED.